Medicinal mushrooms - Halpern, G. M (Progress in Nutrition, 2010)
Summary Mushrooms have been used as medicines by humans for 5,000 years or more. This article deals with five healing mushrooms: maitake, reishi/lingzhi, shiitake, Cordyceps sinensis, and Trametes versicolor [yunzhi]. Many claims are made for medicinal mushrooms. Out of sheer enthusiasm and/or for commercial motives, authors make exaggerated claims. No medicinal mushroom is a cure-all and no mushroom can make the body unassailable to disease. What mushrooms can do is stimulate the immune response, and/or the functions of the body that are already in place for preventing and fighting disease. Maitake is a culinary mushroom that lowers cholesterol, normalizes blood pressure, curbs appetite and helps against diabetes; shiitake, a delicious culinary mushroom, may help prevent AIDS; reishi/lingzhi, the “mushroom of immortality”, has antitumor and antioxidant effects. Cordyceps sinensis is anti-aging and stamina-building, as well at anti-diabetic, and lowers cholesterol. Trametes versicolor, from which Krestin and PSP, anticancer drugs, are derived is being used clinically. These are fascinating providers of health benefits for patients with chronic conditions, and should help a growing aging population without side-effects or obscene pricing. Funghi medicinali Riassunto I funghi sono stati utilizzati in medicina dagli esseri umani per 5.000 anni o più. Questo articolo si occupa di cinque funghi medicinali: maitake, reishi/lingzhi, shiitake, Cordyceps sinensis e Trametes versicolor [yunzhi]. Sull’onda del puro entusiasmo e/o per motivi commerciali, si è scritto molto sull’argomento. I funghi medicinali non sono la panacea per tutti i mali e nessun fungo può rendere il corpo inattaccabile alle malattie. Quello che i funghi possono fare è stimolare la risposta immunitaria, e/o le funzioni del corpo che sono già in atto per prevenire e combattere la malattia. Maitake è un fungo utilizzato in cucina che abbassa il colesterolo, normalizza la pressione sanguigna, frena l’appetito ed è di aiuto nel controllo del diabete; shiitake, ancora un fungo delizioso utilizzato in gastronomia, può aiutare a prevenire l’AIDS; reishi/lingzhi, il “fungo dell’immortalità”, ha effetti antiossidanti e antitumorali. Cordyceps sinensis ha proprietà anti-invecchiamento e di “costruzione”, così come proprietà anti-diabetiche e di abbassamento del colesterolo. Trametes versicolor, da cui sono derivati Krestin e PSP, farmaci antitumorali, è molto utilizzato a livello clinico. Questi elementi sono gli affascinanti fornitori di benefits sanitari a pazienti con patologie croniche, e dovrebbero aiutare la popolazione nell’invecchiamento senza effetti collaterali o prezzi scandalosi.